Elaborar una propuesta turística para el monumento corazón de jesús que contribuye a la promoción del lugar. - Barzola, Kristel (2010)
Monument Heart of Jesus has a Christian and historical value for the city of Guayaquil, is giving elementary highlight the importance it deserves, investigations resulted in the majority of visitors are from Guayaquil, men and women 18 to 35 years old at the scene for tourism, the data collected in the field work has shown the visitors needs such as transportation, as not all visitors have their own vehicle and return the monument to the center d city is difficult because taxis do not circulate frequently. Similarly, another requirement of the visitors is the lack of a guide, a brief explanation about the place, it was constructed, its history and art. In short, the Memorial Heart of Jesus has a pl number of site visits is not significant. That's why we offer recreational and cultural activities so as to cover a certain way the needs of visitors and in turn help increase the flow of visits to the monument "Heart of Jesus."